Placement Optimal of Electric Vehicle Charging Stations Considering Location Constraints in Distribution Networks Integrated Distributed Generation: Published online: 03/02/2026 - Vo, Minh Thien; Doan, Thi Kieu Tien; Nguyen , Van Hau; Le, Quoc Khuong; Vo , Ngoc Dieu (Journal of Technical Education Science, 2026)
Electric vehicles (EVs) are receiving significant attention from countries worldwide due to their outstanding environmental advantages. However, this development has led to the rapid increase and uneven geographical distribution of electric vehicle charging stations (EVCS), which puts pressure on and causes some negative impacts on the power system, particularly the distribution network. Optimizing the placement of EVCS is crucial as it directly affects the efficiency and stability of the power grid, including energy losses, voltage quality, and harmonic distortion. This study focuses on optimizing the placement of EVCS in the distribution network, taking into account cost constraints and EV traffic density, with the objective of minimizing power losses, supporting investment decisions, and ensuring operational indicators of the system. An improved meta-heuristic method combining the Symbiotic Organisms Search (SOS) algorithm and a Chaotic search function (CSOS) is proposed to enhance the search efficiency for solving the problem. The IEEE 34 bus standard distribution network was used to test and evaluate the method through simulations performed in Matlab R2022a. The results from CSOS were assessed and compared with previous studies to demonstrate the superiority and effectiveness of the proposed solution.